Development of MDevSPICE® – the medical device software process assessment framework. Issue 8 (14th July 2015) - Lepmets, Marion; Clarke, Paul; McCaffery, Fergal; Finnegan, Anita; Dorling, Alec; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract Software that is incorporated into a medical device, or which is a standalone medical device in its own right, is of a safety critical nature and subject to regulation from various jurisdictions. In order to satisfy jurisdictional regulations, developers of medical device software adopt standards and guidance provided by international standards bodies and regulators. However, the various standards and guidance documents are often not developed as a single cohesive set resulting in a complex and costly challenge for medical device software developers when complying with regulation. The aim of this paper is to describe the integration of medical device guidance documents and software engineering standards into a unified framework for medical device software process assessment called MDevSPICE®. The paper illustrates the development of both the process reference model and the process assessment model (PAM) of MDevSPICE®. The MDevSPICE® PAM can help software developers to prepare for the regulatory audits, which they must satisfy as a prerequisite to placing their products on the market. The MDevSPICE® PAM can also assist medical device manufacturers to select competent software suppliers. Copyright © 2015 John Wiley & Sons, Ltd.